Answer:
C) 1 1/6 is your answer
Explanation:
First, change each mixed fraction into an improper fraction. To do so, Multiply the whole number with the denominator number, and add the numerator number, setting it over the denominator number.
3 2/6 = (3 x 6 + 2)/6 = 20/6
2 1/6 = (2 x 6 + 1)/6 = 13/6
Next, subtract:
(20/6) - (13/6) = 7/6
Next, simplify, change to a mixed fraction. Note that:
(7/6) = (6/6) + (1/6)
Also note that when the numerator has the same number as the denominator, it = 1.
6/6 = 1
1 + 1/6 = 1 1/6
C) 1 1/6 is your answer
~